Adsorption of Saliva Related Protein on Denture Materials: An X-Ray Photoelectron Spectroscopy and Quartz Crystal Microbalance Study. (4th January 2016) - Miyake, Akiko; Komasa, Satoshi; Hashimoto, Yoshiya; Komasa, Yutaka; Okazaki, Joji
Abstract : The aim of this study was to evaluate the difference in the adsorption behavior of different types of bovine salivary proteins on the PMMA and Ti QCM sensors are fabricated by spin-coating and sputtering onto bare QCM sensors by using QCM and X-ray photoelectron spectroscopy (XPS). SPM, XPS, and contact angle investigations were carried out to determine the chemical composition and surface wettability of the QCM surface. We discuss the quality of each sensor and evaluate the potential of the high-frequency QCM sensors by investigating the binding between the QCM sensor and the proteins albumin and mucin (a salivary-related protein). The SPM image showed a relatively homogeneous surface with nano-order roughness. The XPS survey spectra of the thin films coated on the sensors were similar to the binding energy of the characteristic spectra of PMMA and Ti. Additionally, the amount of salivary-related protein on the PMMA QCM sensor was higher than those on the Ti and Au QCM sensors. The difference of protein adsorption is proposed to be related to the wettability of each material. The PMMA and Ti QCM sensors are useful tools to study the adsorption and desorption of albumin and mucin on denture surfaces.